Black saints in early modern global catholicism - Rowe, Erin Kathleen (Cambridge University Press, 2019)
"In the spring of 2015, I found myself standing outside the walls that led to a courtyard in front of a local church. The doors were supposed to be open according to the hours provided by the tourist office; after waiting a while, I went in search of help. Around the corner was a municipal library, where a librarian offered assistance. As he attempted to find more up-to-date information about the church (in the custody of a confraternity), he asked: "Why do you want to go inside the church?" I told him that I was writing a book about black saints and that I wanted to see the image of Benedict of Palermo inside. Before I finished talking, the man began shaking his head: "No, no, no, there is no black saint in that church. There are no black saints in Antequera." Despite this disappointing news, I decided to go back and wait longer. Eventually, a man with the keys unlocked the door and told me I could go in. And there it was in plain sight - a spectacular sculpture of Benedict of Palermo painted in a monochromatic black pigment. [Plate 1] Plate 1 Saint Benedict of Palermo, Altar of San Diego de Alcalá, eighteenth century. Andalusian school, gilded wood sculpture, 80 x 25 x 25 cm. Andalusia, Spain. Photo: Richard R. Rowe. This incident would not be the only time someone in Spain or Portugal insisted that there was no black saint in a church that housed one. I began to bring a Xerox of the image when I had one to show the person who insisted there was no black saint in that church or museum. Upon viewing the photo, the person would sometimes exclaim: "Oh that image!" as though it had never occurred to him that the sculpture in question was a black saint, despite the dark pigment"--